Current status and outlook of higher education digital transformation in china - Zhang, Chunlei (Review of Artificial Intelligence in Education, 2022)
The requirements of technological advancement, trends in the development of higher education, including the epidemic and other features of the times have prompted the digital transformation of education to become inevitable. Digital transformation can help higher education to create new types of governance capacity and provide quality higher education resources to more students and the public. This article points out that the digital transformation of China’s higher education is characterized by multi-dimensional, multi-level, and multi-regional development, as well as the lack of top-level design and overall planning, and a low level of digital application. Digital governance, digital information platform building and institutional research are key components of the digital transformation. Cooperation between educational administrations, professional societies and universities can accelerate the construction of digital platforms for higher education and enhance the sharing of digital resources. Also, strengthening the research function of institutions to achieve digital strategic goals can help to enhance the practical value of digital transformation in the transformation of higher education.